THE VALIDATION OF THE RESULTS OF MICROARRAY STUDIES OF ASSOCIATION BETWEEN GENE POLYMORPHISMS AND THE FREQUENCY OF RADIATION EXPOSURE MARKERS - M. V. Khalyuzova; N. V. Litvyakov; A. E. Sazonov; Ye. N. Albakh; D. S. Isubakova; A. B. Karpov; R. M. Takhauov (Бюллетень сибирской медицины)
The results from the selective validation research into the association between genetic polymorphisms and the frequency of cytogenetic abnormalities on a large independent sample are analyzed. These polymorphisms have been identified previously during own microarray studies. It has been shown an association with the frequency of dicentric and ring chromosomes induced by radiation exposure. The study was conducted among Siberian Group of Chemical Enterprises healthy employees (n = 573) exposed to professional irradiation in a dose range of 40–400 mSv. We have found that 5 SNP are confirmed to be associated with the frequency of dicentric and ring: INSR rs1051690 – insulin receptor gene; WRNrs2725349 – Werner syndrome gene, RecQ helicase-like; VCAM1 rs1041163 – vascular cell adhesion molecule 1 gene; PCTP rs2114443 – phosphatidylcholine transfer protein gene; TNKS rs7462102 – tankyrase gene; TRF1-interacting ankyrin-related ADP-ribose polymerase. IGF1 rs2373721 – insulin-like growth factor 1 gene has not confirmed to be associated with the frequency of dicentric and ring chromosomes.